Chitosan oligosaccharides prevent doxorubicin-induced oxidative stress and cardiac apoptosis through activating p38 and JNK MAPK mediated Nrf2/ARE pathway. (25th May 2019) - Zhang, Yongtian; Ahmad, Khalil Ali; Khan, Farhan Ullah; Yan, Simin; Ihsan, Awais Ullah; Ding, Qilong
Abstract: Doxorubicin (DOX) is one of the most effective chemotherapeutic drugs; however, the incidence of cardiotoxicity compromises its therapeutic index. Oxidative stress and apoptosis are believed to be involved in DOX-induced cardiotoxicity. Chitosan oligosaccharides (COS), the enzymatic hydrolysates of chitosan, have been reported to possess diverse biological activities including antioxidant and anti-apoptotic properties. The objective of the present study was to investigate the potential role of COS against DOX-induced cardiotoxicity, and the effects of COS on apoptosis and oxidative stress in rats and H9C2 cells. Furthermore, we also shed light on the involved pathways during the whole process. For this purpose, first, we demonstrated that COS exhibited a significant protective effect on cardiac tissue by not only inducing a decrease in body and heart growth but also ameliorated oxidative damage and ECG alterations in DOX-treated rats. Second, we found that COS reversed the decrease of cell viability induced by DOX, reduced the intracellular reactive oxygen species (ROS), increased the mitochondrial membrane potential (MMP) and Bcl-2/Bax ratio. COS treatment also results in reduced caspase-3 and caspase-9 expressions, and an increase in the phosphorylation of MAPKs (mitogen-activated protein kinases) in DOX-exposed H9C2 cells. Additionally, cellular homeostasis was re-established via stabilization of MAPK mediated nuclear factor erythroid 2-related factor 2/antioxidant-response element (Nrf2/ARE) signaling and transcription of downstream cytoprotective genes. In summary, these findings suggest that COS could be a potential candidate for the prevention and treatment of DOX-induced cardiotoxicity. Highlights: COS significantly protects against doxorubicin-induced cardiotoxicity in vivo. COS prevents oxidative stress and cardiac apoptosis induced by doxorubicin. COS prevents doxorubicin cardiotoxicity via p38, JNK MAPK-mediated Nrf2/ARE pathway.